2006
DOI: 10.1080/00958970500404708
|View full text |Cite
|
Sign up to set email alerts
|

Activity of some platinum(II/IV) complexes with edda-type ligands against human adenocarcinoma HeLa cells

Abstract: Cisplatin analogues, cis-dichloro(ethylenediamine-N,N 0 -di-3-propanoic acid)platinum(II) (1) and cis-iodo(ethylenediamine-N,N 0 -di-3-propanoic acid)platinum(II) (2), as well as trans-dichloro-IV) (5) and trans-dibromo(propylenediamine-N,N 0 -diacetato)platinum(IV) (6), -([Pt(H 2 eddp)Cl 2 ], [Pt(Heddp)I], trans-[Pt(eddp)Cl 2 ], trans-[Pt(eddp)Br 2 ], trans-[Pt(pdda)Cl 2 ]and trans-[Pt(pdda)Br 2 ], respectively) were used to assess antitumor selectivity against human adenocarcinoma HeLa cells. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…It was found that Pt II and Pt IV complexes with edda-type ligands have similar cytotoxicity and are generally less efficient than cisplatin. [14] On the other hand, Pt IV complexes with esterified eddatype ligands display greater anticancer activity than corresponding Pt II complexes and cisplatin, [15] causing very rapid ne-…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Pt II and Pt IV complexes with edda-type ligands have similar cytotoxicity and are generally less efficient than cisplatin. [14] On the other hand, Pt IV complexes with esterified eddatype ligands display greater anticancer activity than corresponding Pt II complexes and cisplatin, [15] causing very rapid ne-…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The commercially available cancer treatment drug Oxaliplatin is a platinum complex with the vicinal diamine supporting ligand (1R,2R)-cyclohexane-1,2diamine, 3 and other platinum complexes with chelating diamine supporting ligands are currently being studied further. [5][6][7][8][9][10][11][12] The laboratory synthesis of (racemic) bisindolines has been shown through only a few known methods in the primary literature, all of which are intramolecular reactions (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, a great number of transition metal complexes with EDDA and related ligands have been isolated, and some of them have been also well-characterized using different methods, including X-ray , diffraction, spectroscopic (IR, Raman, NMR, ESR, UV–vis, and CD) techniques, electrochemistry, kinetic and thermodynamic information, , hydrolysis phenomena, as well as condensation reactions . Nowadays, they have given rise to a wide range of applications in chemistry, biology, , and medicine. , …”
Section: Introductionmentioning
confidence: 99%
“…10 Nowadays, they have given rise to a wide range of applications in chemistry, 2 biology, 11,12 and medicine. 13,14 Among these complexes, the octahedral cobalt(III) chelates 15,16 [Co(EDDA-type)(L)] ± containing one of the tetradentate dianion ligands, EDDA (ethylenediamine-N,N′diacetate), DMEDDA (N,N′-dimethylethylenediamine-N,N′diacetate), DEEDDA (N,N′-diethylethylenediamine-N,N′-diacetate), and a bidentate ancillary ligand L are of particular interest, because they have played a prominent role as model systems in the stereochemical study of transition metal complexes.…”
Section: ■ Introductionmentioning
confidence: 99%